L2 cache performance analysis for MPSoC by tag – comparision - A, Jenitha; R, Elumalai (International Journal of Engineering and Technology, 2017)
Memory systems in many applications are becoming increasingly large, contributing to many challenges in the memory management that has led to many method to manage memory. The tag comparison consumes large amount of cache energy. Current methods provide tag comparison cache or failure of the expected cache. Here is proposed an idea based on new call Comparing Tag stages, filter bloom is presented to improve the efficiency of the cache to predict failure and partial tag comparison for the cold line of verification and full comparison check for direct labels. Moreover, the administration of the cache that is filled with cache lines occurs when there is a cache miss. Today's embedded applications use MPSoC. The  MPSoC consists of the following ie more than one  processors, shared memory among the processors available and a global  off-chip memory. Planning of the activities of an integrated application processor and memory partition between processors are two main critical problem. Here, for an integrated application, both task scheduling and partitioning the integrated available L2 cache to reduce the runtime approach is used.